Development of the Book “Matan al-Binā Wa al-Asās” into Student Worksheets on the Chapter of Simple Triliteral Verbs and Increased Triliteral Verbs in the Second Grade at Ma'had at-Taqlīdī Rauḍah al-Ḥikmah al-Waliyah Pango Raya, Banda Aceh. - Fadhil Fadhil; Mukhlisah Mukhlisah (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2020)
The problem in this study is that students are not able to apply the sharf method to identify Fa Fi'il and 'Ain Fi'il and Lam Fi'il in this chapter of the Mujarrad and Tsulasi Mazid and are also unable to identify additional letters in the Tsulasi Mazid chapter and author of the book is not put a distinguishing mark between the original letters and the additional letter in Tsulasi Mazid chapter. The purpose of this study is to find out the steps for developing and effectiveness of the product development of the Book Matan Bina Wal Asas with LKS. The population and sample of this study were all Santri in class 2 in Dayah Raudhatuk Hikmah al-Waliyah in 2018/2019 totaling 57 people. The method used to select samples is a random method. A sample is 30 people. To collect research data using the following tools: Observations, interviews, questionnaires, and T-tests. As for analyzing the data researchers used qualitative and quantitative methods. The result of the study is the analysis of needs, and problems, collecting data, designing a product, revising the product, testing the first product, revising the product, testing the second product, the final revision, and the final product. The product effectiveness of the development of the Book Matan Bina Wal Asas with LKS in the chapter Tsulasi Mujarrad and Tsulasi Mazid in Raudhatul Hikmah Traditional al-Waliyah Pango Raya is a researcher doing statistical calculation whether or not the LKS media are effective? The result of the study shows that the T-count is -9,632 which is smaller than the T-table which is 2,048. So, therefore, accept H0 and reject Ha. Based on the calculation above it can be concluded that the LKS media is effective in learning sharf science.